Any decline in prostate‐specific antigen levels identifies survivors scheduled for prostate‐specific membrane antigen‐directed radioligand therapy. Issue 14 (21st July 2022) - Hartrampf, Philipp E.; Weinzierl, Franz‐Xaver; Seitz, Anna Katharina; Kübler, Hubert; Essler, Markus; Buck, Andreas K.; Werner, Rudolf A.; Bundschuh, Ralph A.
Abstract: Background: Prostate‐specific membrane antigen (PSMA)‐targeted radioligand therapy (RLT) is increasingly incorporated in the therapeutic algorithm of patients with metastatic castration‐resistant prostate cancer (mCRPC). We aimed to elucidate the predictive performance of early biochemical response for overall survival (OS). Materials and Methods: In this bicentric analysis, we included 184 mCRPC patients treated with 177 Lu‐PSMA RLT. Response to treatment was defined as decrease in prostate‐specific antigen (PSA) levels 8 weeks after the first cycle of RLT (any decline or >50% according to Prostate Cancer Working Group 3). OS of responders and nonresponders was then compared using Kaplan–Meier curves and log‐rank comparison. Results: A total of 114/184 patients (62.0%) showed any PSA decline (PSA response >50%, 55/184 [29.9%]). For individuals exhibiting a PSA decline >50%, OS of 19 months was significantly longer relative to nonresponders (13 months; hazard ratio of death [HR] = 0.64, 95% confidence interval [95% CI] = 0.44–0.93; p = 0.02). However, the difference was even more pronounced for any PSA decline, with an OS of 19 months in responders, but only 8 months in nonresponders (HR = 0.39, 95% CI = 0.25–0.60; p < 0.001). Conclusions: In mCRPC patients scheduled for RLT, early biochemical response was tightly linked to prolonged survival, irrespective of the magnitude of PSA decline. As such, even in patients with PSA decrease of less than 50%, RLT should be continued.